Comparative genomic analysis of 142 bacteriophages infecting Salmonella enterica subsp. enterica - Ruimin Gao; Sohail Naushad; Sylvain Moineau; Roger Levesque; Lawrence Goodridge; Dele Ogunremi (BMC Genomics, 2020)
Abstract Background Bacteriophages are bacterial parasites and are considered the most abundant and diverse biological entities on the planet. Previously we identified 154 prophages from 151 serovars of Salmonella enterica subsp. enterica. A detailed analysis of Salmonella prophage genomics is required given the influence of phages on their bacterial hosts and should provide a broader understanding of Salmonella biology and virulence and contribute to the practical applications of phages as vectors and antibacterial agents. Results Here we provide a comparative analysis of the full genome sequences of 142 prophages of Salmonella enterica subsp. enterica which is the full complement of the prophages that could be retrieved from public databases. We discovered extensive variation in genome sizes (ranging from 6.4 to 358.7 kb) and guanine plus cytosine (GC) content (ranging from 35.5 to 65.4%) and observed a linear correlation between the genome size and the number of open reading frames (ORFs). We used three approaches to compare the phage genomes. The NUCmer/MUMmer genome alignment tool was used to evaluate linkages and correlations based on nucleotide identity between genomes. Multiple sequence alignment was performed to calculate genome average nucleotide identity using the Kalgin program. Finally, genome synteny was explored using dot plot analysis. We found that 90 phage genome sequences grouped into 17 distinct clusters while the remaining 52 genomes showed no close relationships with the other phage genomes and are identified as singletons. We generated genome maps using nucleotide and amino acid sequences which allowed protein-coding genes to be sorted into phamilies (phams) using the Phamerator software. Out of 5796 total assigned phamilies, one phamily was observed to be dominant and was found in 49 prophages, or 34.5% of the 142 phages in our collection. A majority of the phamilies, 4330 out of 5796 (74.7%), occurred in just one prophage underscoring the high degree of diversity among Salmonella bacteriophages. Conclusions Based on nucleotide and amino acid sequences, a high diversity was found among Salmonella bacteriophages which validate the use of prophage sequence analysis as a highly discriminatory subtyping tool for Salmonella. Thorough understanding of the conservation and variation of prophage genomic characteristics will facilitate their rational design and use as tools for bacterial strain construction, vector development and as anti-bacterial agents.